Family Functioning and Adolescent Delinquency in Mainland China: Positive Youth Development Attributes as a Mediator - Shek, Daniel T. L.; Leung, Kim H.; Dou, Diya; Zhu, Xiaoqin (Frontiers in Psychiatry, 2022)
According to the positive youth development (PYD) approach, PYD attributes such as psychosocial competencies are developmental assets which can promote the holistic development of adolescents, such as increase in thriving and decrease in risk behavior. Although there are research findings supporting this theoretical proposition, there are several weaknesses in this literature. These include a lack of studies examining family antecedents of PYD attributes and the mediating role of PYD attributes in the relationship between family functioning and adolescent delinquency. There are also few longitudinal studies utilizing large samples and validated measures of family functioning and PYD attributes in the scientific literature. In this study, we examined the predictive effect of family functioning on adolescent delinquency and the mediating role of PYD attributes. Using a short-term longitudinal study in Sichuan, China, we collected two waves of data from 4,981 adolescents aged 11 and above, with 6 months between the two waves. Analyses using structural equation modeling showed that family functioning at Wave 1 negatively predicted the level of and change in delinquent behavior at Wave 2, with PYD attributes at Wave 2 as a mediating factor. The present study enriches the conceptual framework on the role of family functioning and PYD attributes in adolescent delinquent behavior. The findings also suggest that strengthening family functioning and PYD attributes would protect adolescents from engaging in delinquent acts.